Separation and determination of the enantiomers of lactic acid and 2‐hydroxyglutaric acid by chiral derivatization combined with gas chromatography and mass spectrometry. Issue 12 (30th May 2018) - Ding, Xuemei; Lin, Shuhai; Weng, Hongbo; Liang, Jianying
Abstract: Lactic acid and 2‐hydroxyglutaric acid are chiral metabolites that have two distinctd‐ andl ‐enantiomers with distinct biochemical properties. Perturbations of a single enantiomeric form have been found to be closely related to certain diseases. Therefore, the ability to differentiate thed andl enantiomers is important for these disease studies. Herein, we describe a method for the separation and determination of lactic acid and 2‐hydroxyglutaric acid enantiomers by chiral derivatization (withl‐ menthol and acetyl chloride) combined with gas chromatography and mass spectrometry. The two pairs of above‐mentioned enantiomers exhibited linear calibration curves with a correlation coefficient ( R 2 ) exceeding 0.99. The measured data were accurate in the acceptable recovery range of 88.17–102.30% with inter‐ and intraday precisions (relative standard deviations) in the range of 4.23–17.26%. The limits of detection ford‐ lactic acid, l‐ lactic acid, d‐ 2‐hydroxyglutaric acid, andl‐ 2‐hydroxyglutaric acid were 0.13, 0.11, 1.12, and 1.16 μM, respectively. This method was successfully applied to analyze mouse plasma. Thed‐ lactic acid levels in type 2 diabetes mellitus mouse plasma were observed to be significantly higher ( P < 0.05, t ‐test) than those of normal mice, suggesting thatd‐ lactic acid may serve as an indicator for type 2 diabetes mellitus.